2019
DOI: 10.1002/ptr.6534
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Seidlitzia rosmarinus (eshnan) on the prevention of recurrent cystitis in women of reproductive age: A randomized, controlled, clinical trial

Abstract: The World Health Organization has recommended herbal medicine for treatment and control of recurrent cystitis. This study was conducted to determine effect of eshnan on the prevention of recurrent cystitis. The present triple-blind clinical trial was conducted on 126 women (63 women per group) with recurrent cystitis. The participants were assigned to the intervention and control groups. Three 500-mg eshnan or placebo tablets were taken orally with a glass full of water by the participants half an hour after e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…A study showed that it is effective against Recurrent cystitis Mahin Kmaliford et al [26] Foodanj Mentha arvensis Melastomaceae Aerial, leaf Carminative, diuretic, emmenagogue Antimicrobial, anti-spasmodic, antioxidant, emmenagogue activity Peyman Mikaili et al [27] Hilteet…”
Section: Emmenagogue Abortifacient Detergentmentioning
confidence: 99%
“…A study showed that it is effective against Recurrent cystitis Mahin Kmaliford et al [26] Foodanj Mentha arvensis Melastomaceae Aerial, leaf Carminative, diuretic, emmenagogue Antimicrobial, anti-spasmodic, antioxidant, emmenagogue activity Peyman Mikaili et al [27] Hilteet…”
Section: Emmenagogue Abortifacient Detergentmentioning
confidence: 99%